Controlling Suhu dan Kelembapan dengan Pengembangan Sirkulasi Udara pada Kandang Peternakan Ayam Broiler - Juwita Intan Nur Alam; Jentot Tugiyono; Alkautsar Rahman (Journal Data Science, Technology, Informatics and Security, 2023)
This research aims to develop a temperature and humidity control system with the development of air circulation in broiler chicken farm cages. The use of temperature and humidity sensors integrated with automatic control, as well as the Android monitoring interface, is used to create an optimal environment for broiler chickens. Sensor data is sent to the cloud platform for analysis and visualization. The results showed that the system can maintain the temperature and humidity within the desired range, contributing to the productivity and well-being of broiler chickens. With further development, this technology has the potential to improve livestock efficiency and management.